Impact of Changing Arctic Sea Ice Extent, Sea Ice Age, and Snow Depth on Sea Salt Aerosol From Blowing Snow and the Open Ocean for 1980–2017. Issue 3 (1st February 2023) - Confer, K. L.; Jaeglé, L.; Liston, G. E.; Sharma, S.; Nandan, V.; Yackel, J.; Ewert, M.; Horowitz, H. M.
Abstract: We evaluate the effects of rapidly changing Arctic sea ice conditions on sea salt aerosols (SSA) produced by oceanic wave‐breaking and the sublimation of wind‐lofted salty blowing snow on sea ice. We use the GEOS‐Chem chemical transport model to assess the influence of changing extent of the open ocean, multi‐year sea ice (MYI), first‐year sea ice (FYI), and snow depths on SSA emissions for 1980–2017. We combine snow depths from the Lagrangian snow‐evolution model (SnowModel‐LG) together with an empirically‐derived snow salinity function of snow depth to derive spatially and temporally varying snow surface salinity over Arctic FYI. We find that pan‐Arctic SSA surface mass concentrations have increased by 6%–12% decade −1 during the cold season (November–April) and by 7%–11% decade −1 during the warm season (May–October). The cold season trend is due to increasing blowing snow SSA originating from FYI: as MYI is replaced by FYI with thinning snow depths, snow surface salinity increases by more than 11% decade −1 . During the warm season, rapid sea ice loss and thus increasing open ocean SSA are the cause of modeled SSA trends. Observations of SSA mass concentrations at Alert, Canada display positive trends during the cold season (10%–12% decade −1 ), consistent with our pan‐Arctic simulations. During fall, Alert observations show a negative trend (−18% decade −1 ), due to locally decreasing wind speeds and thus lower open ocean emissions. These significant changes in SSA concentrations could potentially affect past and future bromine explosions and Arctic climate feedbacks. Plain Language Summary: Suspended sea salt particles affect the climate and chemistry of the atmosphere. The main source of these particles is ocean wave breaking. In polar regions an additional source is the wind lofting of salty snow that is present on top of sea ice. Here we use model simulations to examine how changing Arctic conditions have impacted sea salt particles in the atmosphere. Our simulations show that the concentrations of sea salt particles have increased by more than 6% per decade over the 1980–2017 period. During cold months, this increase is due to saltier blowing snow particles as older sea ice with less salty snow is being replaced by younger sea ice with more salty snow. During warmer months, this increase is the result of larger open ocean emissions as sea ice is melting. These changes in sea salt particles could potentially affect Arctic bromine activation and climate. Key Points: Model predicts pan‐Arctic increase in sea salt aerosol (SSA) concentrations by 6%–12% decade −1 for 1980–2017 Younger Arctic sea ice with thinner and saltier snow cause increasing blowing snow SSA emissions in winter‐spring During summer‐fall, rapidly diminishing sea ice extent results in increasing open ocean SSA emissions